Transporter protein expression and localization in murine mammary epithelial HC11 cells - Yagdiran, Yagmur (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2012)
Milk is the sole food for breast-fed infants and a significant source of nutrition for consumers of dairy products. It has a very complex composition containing both macronutrients and micronutrients needed for growth and development. Drugs, carcinogens and environmental toxins can be secreted in milk posing a potential health risk for breast-fed infants and milk consumers. Active transport by membrane proteins in secretory mammary epithelial cells can explain this process. Several membrane protein transporters from different protein families (Solute carrier (SLC) and ATP-binding cassette (ABC) super families) mediate transport of a wide range of different compounds. The major purpose of this project was to investigate transporter protein expression of mouse Bcrp, Mdr1, Octn1 and Oatp3 (Oatp1a5) by using a murine mammary epithelial HC11 cell line. Differentiated HC11 cells featuring a milk protein synthesizing and secreting phenotype were used in western blot experiments to detect the proteins of interest. In this cell model it was possible to detect upregulation of membrane transporters mouse Bcrp and Octn1 as a result of the differentiation. In addition, immunohistochemistry on lactating mouse mammary gland tissues was performed to detect the localization of mouse Octn1. Octn1 was localized at the apical membrane of mammary epithelial cells supporting the theory that it plays a role in the transport of carnitine into milk. The impact of lipopolysaccharide (LPS) treatment, mimicking mammary inflammation, on protein expression of transporters in secreting HC11 cells were examined by western blotting. However, at the LPS concentration used no effects were detected. This study provides basic tools for understanding the nature of secretion of nutrients and nonnutrients to milk by membrane transporters. Further investigations are required to understand the correlation between protein expression and function of membrane transporters in secreting HC11 cells.